Chd1 chromatin remodelers maintain nucleosome organization and repress cryptic transcription - Hennig, Bianca P.; Bendrin, Katja; Zhou, Yang; Fischer, Tamás (EMBO reports, 2012)
Chromatin organization is essential for defining transcription units and maintaining genomic integrity in eukaryotes. In this study, we found that deletion of the Schizosaccharomyces pombe Chd1 chromatin remodelers, hrp1 and hrp3, causes strong, genome‐wide accumulation of antisense transcripts. Nucleosome mapping revealed a specific role for Chd1 remodelers in the positioning of nucleosomes in gene coding regions. Other mutations associated with enhanced cryptic transcription activity, such as set2Δ, alp13Δ and FACT complex subunit pob3Δ, did not, or only mildly, affect nucleosome positioning. These data indicate several mechanisms in the repression of cryptic promoter activity in eukaryotic cells.